ChemInform Abstract: Synthesis, Characterization and Modelling of a Ferromagnetically Coupled Chromium(III) Dimer: Di‐μ‐hydroxobis[tetrakis(isothiocyanato)chromate(III)]. Issue 10 (March 2015) - Morsing, Thorbjoern J.; Weihe, Hoegni; Bendix, Jesper
Abstract (Ph4P)4 [(SCN)4Cr(OH)2Cr(NCS)4]·2MeCN (I) is synthesized from a solution of [(MeCN)5CrOCr(MeCN)5](BF4)2 and (Ph4P)SCN (obtained from an aqueous mixture of (Ph4P)Cl and NaSCN in 91% yield) in MeCN (40 °C, 36% yield).